Traffic on the Croatian Inland Waterways in the Context of the European Programme Naiades - Ivaković, Čedomir; Rogić, Kristijan; Orlić Protega, Adrijana (Promet - Traffic&Transportation, 2008)
On 17 January 2006, the European Commission acceptedthe Action Programme NAIADES for the promotion of navigationon the inland waterways on the European Union territoryfor the period 2006 - 2013. The programme has been harmonizedwith the White Paper guidelines - the ’European trafficpolicy for 2010: time for decision’, and recommends joining ofthe countries who are currently not the EU members, which includesCroatia.111e NAIADES action programme is based on five strategic,interdependent areas: market - improvement of market conditions;fleet -fleet modernization; personnel policy - developmentof human resources; image - creation of a better imageand infrastructure- realization of infrastructure preconditions.This paper analyses the basic hypotheses of the NAIADESaction programme in order to shed light on the possible implementationof its guidelines regarding the development and promotionof traffic on the Croatian inland waterways.